Agricultural Growth and Rural Poverty Reduction in India Targeting Investments and Input Subsidies - Bathla, Seema; Joshi, Pramod Kumar; Kumar, Anjani (India Studies in Business and Economics, 2020)
XVIII, 132 p. 14 illus., 10 illus. in color.